Migfilin promotes migration and invasion in glioma by driving EGFR and MMP-2 signalings: A positive feedback loop regulation. (20th December 2017) - Ou, Yunwei; Wu, Qingnan; Wu, Chuanyue; Liu, Xuefeng; Song, Yongmei; Zhan, Qimin
Abstract: Glioma is the most common type of primary brain tumors in the central nervous system (CNS). Migfilin occurs in human glioma and enhances cellular motility via the epidermal growth factor receptor (EGFR) pathway. However, the underlying molecular mechanism is not fully understood. In this study, we found that Migfilin promoted matrix metalloproteinase-2 (MMP-2) activity, and restrained the expression of tissue inhibitor of metalloproteinase 2 (TIMP2), which is an MMP-2 inhibitor. Functional and structural studies showed that the LIM1 domain of Migfilin was required for Migfilin-mediated TIMP2 expression inhibition and MMP-2 activity, and was also necessary in promoting cell motility. Furthermore, Migfilin-induced EGFR phosphorylation was greatly reduced by MMP-2 inhibitor (GM6001) or siRNA, while Migfilin-induced MMP-2 activation was also blocked by the EGFR inhibitor (AG1478) or siRNA. MMP-2 and EGFR inhibitors and their siRNAs can block Migfilin-induced migration and invasion, respectively. These results demonstrated that EGFR and MMP-2 signalings may form a positive feedback loop to enhance Migfilin-induced migration and invasion. Finally, we detected that the expression of Migfilin, EGFR phosphorylation (Tyr1173) and MMP-2 activity had a positive correlation in the clinical glioma sample. Taken together, these results suggest that Migfilin is a critical regulator in cellular motility by driving the EGFR-MMP-2 feedback loop, and may be considered as a potential therapeutic target in glioma.